Pengaruh Dana Alokasi Umum Dan Dana Alokasi Khusus Terhadap Tingkat Kemandirian Keuangan Daerah Di Kota Pematangsiantar - Eka Pratiwi Septania Parapat; Debora Silvia Hutagalung; Eve Ida Malau (Jurnal Akuntansi Dan Manajemen Indonesia (JAMIN), 2021)
This study aims to determine the effect of the General Allocation Fund and the Special Allocation Fund on the Level of Regional Financial Independence in Pematangsiantar City. This type of research is causal associative research. This research was conducted for the period 2011-2016. The type of data used is secondary data. Data obtained through the Department of Revenue and Financial Management of Regional Assets. The data analyzed in this study were processed from the Regional Revenue and Expenditure Budget Report (APBD) and the Regional Revenue and Expenditure Budget Realization Report (APBD). Hypothesis testing in this study used multiple linear regression, t test, F test and coefficient of determination test. The results of the analysis show that partially the General Allocation Fund and the Special Allocation Fund have a significant negative effect on the level of Regional Financial Independence. Simultaneously the General Allocation Fund and the Special Allocation Fund also have a significant negative effect on Regional Financial Independence